KOLABORASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN PROBLEMBASED LEARNING (PBL) UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN ADMINISTRASI HUMAS & KEPROTOKOLAN KELAS XI AP 2 SMK NEGERI - Singgih Rakasiwi (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2016)
The objectives of this research are to investigate the collaboration of the cooperative learning model of the NHT type andthe PBL learning model to improve the learning activeness and resultin the Public Relation and Protocol subject matter of the students inGrade XI Office Administration 2 of State Vocational High School 1of Boyolali in Academic Year 2015 / 2016. This research used theclassroom action research method with two cycles. Each cycleconsisted of four phases, namely: (1) planning, (2) implementation,(3) observation, and (4) reflection. Its subject was the students asmany as 32 in Grade XI Office Administration of State VocationalHigh School 1 of Boyolali. The data sources of the research were ateacher and the students. The data of research were collected throughobservation, test, and documentation. They were validated by usingthe data collection triangulation, and method triangulation, andcontent validity. The data were analyzed by using the descriptivecomparative model of analysis and the critical model of analysis. Thestudents‟ learning activeness in the visual aspect was 13.79% in Precycle. Then it became 62.50% in Cycle I and 87.50% in Cycle II respectively. Furthermore, the students‟ learning activeness in the oral activity aspect was 20.69% in Pre-cycle. Next, it became 62.50% in Cycle I and 90.63%in Cycle II. In addition, the students‟ learning activeness in the listening activity aspect was 17.24% in Pre-cycle. Then it became 68.75% in Cycle I and 87.50% in Cycle II. Finally, the students‟ learning activeness in the writing activity aspect was 27.69% in Pre-cycle. Then, it became 81.25% in Cycle I and 100% in Cycle II. The percentage of the students who attained the minimum learning completeness was 46.87% with the average score of 84.74 in Precycle. Then, it became 75.00% with the average score of 85.63 in Cycle I and 93.75% with the average score of 96,25 in Cycle II respectively.